Electro-cortical measures during visual and kinesthetic imagery performance following visual- and auditory-guided instructions - Cremades, J. G. (International Journal of Sport and Exercise Psychology, 2016)
Electroencephalography (EEG) measures can provide extensive and detailed knowledge of how the brain works during imagery. Prior to imagery performance, individuals may acquire information on how to imagine the movement through either visual or auditory instructions. The purpose of this study was to determine differences in cerebral cortical activation during kinesthetic and visual imagery performance while following visual- and audio-guided imagery instructions. EEG recordings were collected from 28 participants and guided imagery instructions were given in two versions: audio and visual. The results revealed that lower alpha values (8-10 Hz) were greater when participants were performing kinesthetic imagery following auditory instructions as opposed to following visual instructions. Furthermore, lower alpha values were greater at the right hemisphere than the left hemisphere and greater at the right temporal site than the left temporal site. In the upper alpha band (11-13 Hz), results showed that values were greater at the temporal site in the right hemisphere than the temporal site in the left hemisphere. In addition, upper alpha values were greater at the right hemisphere than the left hemisphere and greater at the right temporal site than the left temporal site. The findings of this study suggest that electro-cortical measures can detect differences of the processes involved during guided imagery performance while following either audio or video instructions. In the applied setting, practitioners can implement neurofeedback techniques to assess the specific mental effort required by individuals following guided instructions to perform imagery.